Strengthening Tanzania's innovation ecosystem for climate-resilient agriculture - Mukuna, Eliaza; Kariuki, Wangari; Khader, Taija (2025)
The AgriTech4Tanzania Consultation Workshop was organized by the Alliance of Bioversity International and CIAT through the CGIAR Accelerate for Impact Platform (A4IP) in collaboration with Tanzania Agricultural Research Institute (TARI), the United Nations Industrial Development Organization (UNIDO), Shamba Box, and funded by the Italian Ministry of Foreign Affairs and International Cooperation. The event brought together over 100 development partners, entrepreneurs, farmers, policymakers, and researchers, to advance agricultural innovation in Tanzania, recognizing the sector’s pivotal role in the economy, food security, and inclusive growth.